PENGARUH EKUITAS MEREK DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN JASA MASKAPAI PENERBANGAN GARUDA INDONESIA - Shandra Kusuma Dewi; Apriatni Endang Prihartini; Sari Listyorini (Universitas Diponegoro, 2013)
This research aims to know the brand equity effect which is consists of four brand equity dimension, they are ; brand awareness; brand association; perceived quality and brand loyalty; and promotion to the decision of utilizing the Garuda Indonesia flight company service. The hypothesis is there was brand equity variable effect and promotion to the decision of utilizing the Garuda Indonesia flight company service. The type of this research is the explanatory research,the sample collecting technique is purposing sampling technique by 100 samples as the respondent. Hypotheses tested by correlation coefficient, simple linear regression, multiple linear regression, t test, F test, and determination coefficient which is supported by SPSS for Windows as the analysis method. The result of this research shows that equity brand variable has significant effect to the decision of utilizing the Garuda Indonesia flight company service 37,4 %. The promotion variable has also significant to the decision of utilizing the Garuda Indonesia flight company service 30,3 %. Equity brand variable and promotion have effect to the purchasing decision 45,4 %.